Developmental TVET Rhetoric In-Action: The White Paper for Post-School Education and Training in South Africa - Salim Akoojee (European Research Network Vocational Education and Training (VETNET), 2016)
This paper explores the extent to which latest developments in the Technical and Vocational Education and Training System in South Africa respond to key principles espoused for a developmental, democratic and inclusionary ideal. The White Paper for post school education and training approved by Cabinet in November, 2013 is referred to by the Minister as the "definitive statement of the governments vision for the post school system" and as such represents a crucial strategy document intended to chart the TVET direction to 2030. Using key theoretical constructs from development theory, this paper provides an assessment of the TVET strategy contained is the paper and explores the extent to which it does respond to the agenda defined by the promise. It is argued that the challenges outlined are not yet able to provide the blueprint for a TVET transformative vision. It is concluded that while the development rhetoric contained in the paper is plausible, the creative tinkering of the system is unlikely to lead to the radical revisioning necessary for a truly transformative TVET system. The underlying assumptions regarding purpose, impact and outcome will need to be carefully reconsidered if the system is to be responsive to the promises of the democratic developmental ideal to which the government is committed.